ECLIPTA ALBA AMELIORATES CARBON TETRACHLORIDE-INDUCED LIPID PEROXIDATION: AN IN VITRO STUDY - MONALI PATEL; R. J. VERMA (International Journal of Pharma and Bio Sciences, 2013)
The present investigation was an attempt to evaluate the possible ameliorative effect of Eclipta alba on carbon tetrachloride (CCl4) – induced lipid peroxidation in liver of mice in vitro. Antioxidant activity of medicinally important plant Eclipta alba was determined by DPPH – radical scavenging activity. Liver tissue was collected from healthy Swiss albino female mice weighing 30-35 gm. Liver homogenates were prepared and used for various treatments (CCl4 with and without hydro-alcoholic extract of Eclipta alba ) followed by analysis of lipid peroxidation and protein content. The results revealed that addition of CCl4 (5-50 µg/ml) to liver homogenate caused a significant increase in lipid peroxidation which was maximum at 10 µg/ml. An addition of hydro-alcoholic extract of Eclipta alba (25-150 µg/ml) significantly reduced CCl4 (10 µg/ml) - induced lipid peroxidation in concentration-dependent manner. The result was compared with standard drug Liv. 52. The study confirmed the ameliorative effect of the hydro-alcoholic extract of Eclipta alba even higher than the Liv. 52, which may be attributed due to its antioxidative property as revealed by DPPH radical scavenging activity measured.